2022
DOI: 10.37934/arfmts.93.2.111124
|View full text |Cite
|
Sign up to set email alerts
|

Quadratic Convective Nanofluid Flow at a Three-Dimensional Stagnation Point with the g-Jitter Effect

Abstract: The nonlinear density variation with temperature happens in many thermal applications like solar collectors, energy production, heat exchangers, and combustions, and it gives a significant impact on heat transfer and fluid flows. Thus, a nonlinear convective of an unsteady stagnation point flow under the influence of gravity modulation in the presence of water-based nanoparticles alumina (Al2O3) is studied here. Suitable variables are utilized to reduce the highly coupled nonlinear governing equations into a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Ostrach (1952) who started the convection flow study, used an integral method to make a technical note on transient free convection flow's similarity solution past a semi-infinite vertical plate. Rawi et al (2016;2018) studied the effect of g-jitter on the mixed convection flow of Jeffrey fluid and micropolar nanofluids past an inclined stretching sheet with the presence of nanoparticles, while Hamdan et al (2020) and Rosaidi et al (2022) conducted their research based on free convection flow fluid since it is simpler to analyses the behaviors of the magnetic nanofluids because it naturally happens without affected by any external forces. Heat transfer analysis with convective boundary conditions is evoked in processes including high temperatures such as thermal energy storage, gas turbines, and nuclear plants (Akbar et al, 2013;Nadeem et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Ostrach (1952) who started the convection flow study, used an integral method to make a technical note on transient free convection flow's similarity solution past a semi-infinite vertical plate. Rawi et al (2016;2018) studied the effect of g-jitter on the mixed convection flow of Jeffrey fluid and micropolar nanofluids past an inclined stretching sheet with the presence of nanoparticles, while Hamdan et al (2020) and Rosaidi et al (2022) conducted their research based on free convection flow fluid since it is simpler to analyses the behaviors of the magnetic nanofluids because it naturally happens without affected by any external forces. Heat transfer analysis with convective boundary conditions is evoked in processes including high temperatures such as thermal energy storage, gas turbines, and nuclear plants (Akbar et al, 2013;Nadeem et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…THNFs exhibited enhanced heat transfer rates and exerted a greater influence on surfaces compared to hybrid and regular nanofluids. Others researcher study on magnetic impact in the various problem such as [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…The study found that the Grashof number has improved the velocity field and lowered the momentum boundary layer thickness. The study on free convection was rapidly established by considering the different problems and situations by Hamdan et al (2020) and Mohamad et al (2022). They found that the Grashof number has a significant impact on the velocity and momentum boundary layer thickness.…”
Section: Introductionmentioning
confidence: 99%